Konstruksi Penilaian Membaca Pembelajaran Bahasa Indonesia Kelas X SMA Negeri Se-Kecamatan Tenayan Raya - Erlinawati; Sukenti, Desi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
The research objectives are 1) To determine the construction of the assessment of reading Indonesian saga for class X SMA Negeri Tenayan Raya District. 2) to determine the construction of the assessment of reading Indonesian poetry for class X SMA Negeri Tenayan Raya Pekanbaru. The research method is a qualitative type of phenomenology. The theory used is Setiadi (2016), Yunus (2012), Suherli (2017), Djiwandono (2011), Zainal (2017). The data sources for this study were 5 Indonesian language teachers. In-depth interview data collection techniques and documentation. Phenomenological data analysis techniques. The results of the research on the construction of saga reading assessments are speech sounds, words, sentences, letters, language, reading, paying attention to reading pauses, sentence breaks, paragraph breaks, pronouncing sentence contents, letter contents, punctuation marks, appreciating the content. While the construction of the assessment of reading poetry is the sound of diction, sound, letters, sentences, rhyme, rhythm, stanzas, figure of speech, confidence, style, appreciation. The conclusion of this research is that the construction of the assessment of reading Indonesian saga in grade X is formed from thirteen sub themes, while the construction of the assessment of reading poetry consists of eleven sub themes.